2010
DOI: 10.1900/rds.2010.7.112
|View full text |Cite
|
Sign up to set email alerts
|

The Quest for Tissue Stem Cells in the Pancreas and Other Organs, and their Application in Beta-Cell Replacement

Abstract: ■ AbstractAdult stem cell research has drawn a lot of attention by many researchers, due to its medical hope of cell replacement or regenerative therapy for diabetes patients. Despite the many research efforts to date, there is no consensus on the existence of stem cells in adult pancreas. Genetic lineage tracing experiments have put into serious doubt whether β-cell neogenesis from stem/progenitor cells takes place postnatally. Different in vitro experiments have suggested centroacinar, ductal, acinar, stella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Since CSC are very similar to non-malignant stem cells, it is suggested that CSC can be created by oncogenic transformation of tissue-specific stem cells [270,271]. However, in it is still unclear whether an adult stem cell pool resides in the pancreas [272], posing the possibility that there may be an alternative source for pancreatic CSC. Besides, evidence indicates that CSC are not necessarily derived from normal stem cells.…”
Section: Pancreatic Cancer Stem Cells and Emtmentioning
confidence: 99%
“…Since CSC are very similar to non-malignant stem cells, it is suggested that CSC can be created by oncogenic transformation of tissue-specific stem cells [270,271]. However, in it is still unclear whether an adult stem cell pool resides in the pancreas [272], posing the possibility that there may be an alternative source for pancreatic CSC. Besides, evidence indicates that CSC are not necessarily derived from normal stem cells.…”
Section: Pancreatic Cancer Stem Cells and Emtmentioning
confidence: 99%
“…The generation of functional pancreatic beta-cells to compensate for the short supply of donor human islets has long been regarded as a potential solution for the treatment of diabetes 39 . To this goal, great efforts have been made to generate functional beta-cells from non-beta cell sources, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Those of Swenson [] found that acinar cells derive from a single stem cell, whereas islets derive from more than one []. Importantly, stem cells are found in postnatal liver [] but are very rare in postnatal pancreas []. This paradox has been clarified recently with the discovery that pancreatic stem cells are not in the pancreas but rather in the biliary tree, particularly in the hepato‐pancreatic common duct [].…”
Section: Epithelial–mesenchymal Maturational Lineagesmentioning
confidence: 99%